Linking climate change and health outcomes: Examining the relationship between temperature, precipitation and birth weight in Africa. (November 2015) - Grace, Kathryn; Davenport, Frank; Hanson, Heidi; Funk, Christopher; Shukla, Shraddhanand
Highlights: Temperature and precipitation may impact birth weight outcomes. Maternal nutrition experiences may link birth weight and climate variability in poor countries. Birth weight outcomes are impacted by changes in the number of hot days and precipitation amounts. The linkages between birth weight and climate exist apart from socio-economic variabilities. Abstract: This paper examined the relationship between birth weight, precipitation, and temperature in 19 African countries. We matched recorded birth weights from Demographic and Health Surveys covering 1986 through 2010 with gridded monthly precipitation and temperature data derived from satellite and ground-based weather stations. Observed weather patterns during various stages of pregnancy were also used to examine the effect of temperature and precipitation on birth weight outcomes. In our empirical model we allowed the effect of weather factors to vary by the dominant food production strategy (livelihood zone) in a given region as well as by household wealth, mother's education and birth season. This allowed us to determine if certain populations are more or less vulnerable to unexpected weather changes after adjusting for known covariates. Finally we measured effect size by observing differences in birth weight outcomes in women who have one low birth weight experience and at least one healthy birth weight baby. The results indicated that climate does indeed impact birth weight and at a level comparable, in some cases, to the impact of increasing women's education or household electricity status.